Mapping Two Decades of Innovation Management Research: A Bibliometric Review from Scopus (2005–2025) - Rahmi Widyanti; Basuki Basuki; Mohammad Zainul; Idzani Muttaqin (At-Tadbir : jurnal ilmiah manajemen, 2026)
This bibliometric review systematically mapped the intellectual landscape of innovation management research as indexed in the Scopus database from 2005 to 2025. The study's overarching purpose was to provide comprehensive, objective, and timely insights into the field's evolution by identifying growth trajectories, influential entities, dominant thematic clusters, and collaboration dynamics1. Employing a quantitative bibliometric design, data was meticulously collected from 2170 journal articles, adhering to PRISMA guidelines and analysed using Bibliophagy-R web based. Key findings revealed a rapidly expanding research domain with a 26.49% annual growth rate and an average of 16.12 citations per document.  Sustainability (Switzerland) emerged as the most prolific source, reflecting a strong convergence of innovation with sustainability. East Asian scholars, particularly those with Chinese surnames, were highly productive, dominating author contribution lists and forming extensive collaborative networks. The analysis of highly cited documents further underscored the impact of sustainability-focused innovation research. International collaboration, particularly involving China, North America, and Europe, was substantial, accounting for over a quarter of co-authored works. This study illuminates the dynamic progression of innovation management, offering a structured overview crucial for shaping future research agendas responsive to contemporary global challenges.